Carex_curvula - Armbruster, Georg F.J.; Gielly, Ludovic; Taberlet, Pierre; Stöcklin, Jürg (Dryad Digital Repository, 2011)
AFLP data: Matrix with samples (rows) and markers (columns), 1 indicating presence of AFLP-fragment, 0 indicating absence of AFLP-fragment.